2011
DOI: 10.1007/s00198-011-1607-0
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of bone turnover by B-cell depletion in patients with rheumatoid arthritis

Abstract: In conclusion, we have found that B-cell depletion increases bone formation and decreases bone resorption in RA patients; this may be a direct effect on osteoblasts and osteoclasts, respectively, and be at least partially explained by the decreased inflammation and disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 28 publications
2
27
0
3
Order By: Relevance
“…Consistent with our results, previous studies have shown that serum levels of osteocalcin are negatively correlated with disease activity in RA patients 46 47. Of note, one other study in 46 RA patients did not demonstrate a change in osteocalcin 6 months after rituximab treatment;48 the reason for this discrepancy is at present unclear. The fact that serum NTx did not change can perhaps be explained by the long disease duration of our cohort, as previous studies have shown that carboxy terminal telopeptide (a comparable bone resorption marker) levels are decreased in RA patients with a disease duration of more than 10 years.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with our results, previous studies have shown that serum levels of osteocalcin are negatively correlated with disease activity in RA patients 46 47. Of note, one other study in 46 RA patients did not demonstrate a change in osteocalcin 6 months after rituximab treatment;48 the reason for this discrepancy is at present unclear. The fact that serum NTx did not change can perhaps be explained by the long disease duration of our cohort, as previous studies have shown that carboxy terminal telopeptide (a comparable bone resorption marker) levels are decreased in RA patients with a disease duration of more than 10 years.…”
Section: Discussionsupporting
confidence: 87%
“…A recent article showed that mice lacking RANKL in B cells were partially protected from ovariectomy-induced loss of cancerous bone [29]. The role of B lymphocytes has also been evaluated in diseases characterized by focal bone loss, such as periodontal inflammation [14, 30, 31] and rheumatoid arthritis [16, 32]. In rheumatoid arthritis, a recent study showed that B cell depletion ameliorates suppressed bone turnover [29].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, changes in several B lymphocyte populations in patients affected by postmenopausal osteoporosis regardless of their estrogen status have been shown. 51 The role of B cells in the control of bone turnover has been studied in other diseases that affect bone, such as RA 48,52 and periodontal inflammation. 53 These studies suggest that B cells may be involved in the control of bone turnover in humans as well, mainly by the production of cytokines such as OPG and RANKL.…”
Section: Inflammatory Diseases Immune System and Bonementioning
confidence: 99%